Whose surgery is this? Endometriosis of the round ligament - Michele Mongelli,; Cormio, Gennaro; Giudice, Giuseppe; Legge, Francesco; Resta, Leonardo; Lambo, Michele; Leone, Luca; Marinaccio, Marco; Loizzi, Vera; Arezzo, Francesca; Cicinelli, Ettore; Cataldo, Viviana (Acta Biomedica Atenei Parmensis, 2022)
We report two cases of endometriosis of the round ligament in a 37 and 26 - years old women, with a lump in their right groin and catamenial pain referred to plastic surgery department. MRI showed in both cases nodular lesion in the right inguinal region. The patological examination of the surgical specimen revealed endometriosis of the round ligament.The presence of a groin mass with pain increasing during the menstrual period must raise the suspicion of inguinal endometriosis and a gynecological evaluation is essential to provide a correct management of this rare condition.